2019
DOI: 10.1002/ajim.22967
|View full text |Cite
|
Sign up to set email alerts
|

Health effects from unintentional occupational exposure to opioids among law enforcement officers: Two case investigations

Abstract: Recent increases in the rate of drug overdose-related deaths, the emergence of potent opioids such as carfentanil, and media reports of incidents have raised concerns about the potential for work-related exposure to a variety of illicit drugs among law enforcement officers (LEOs), other emergency responders, and other workers in the United States. To characterize the risk associated with unintentional occupational exposure to drugs, we retrospectively investigated two incidents that occurred in 2017 and 2018 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
6
2
Order By: Relevance
“…After a multiagency operation, Agency officials became concerned because a large proportion of LEOs who participated became ill over the course of several days. The types of symptoms and the timing of symptom onset were not consistent with symptoms reported after illicit drug exposure in other recent HHEs [Chiu et al 2019] or symptoms reported from exposures to other substances identified in the residence. While almost one third of symptomatic LEOs met the case definition for influenza-like illness, the group of symptomatic LEOs most likely had more than one type of illness.…”
Section: Discussioncontrasting
confidence: 61%
“…After a multiagency operation, Agency officials became concerned because a large proportion of LEOs who participated became ill over the course of several days. The types of symptoms and the timing of symptom onset were not consistent with symptoms reported after illicit drug exposure in other recent HHEs [Chiu et al 2019] or symptoms reported from exposures to other substances identified in the residence. While almost one third of symptomatic LEOs met the case definition for influenza-like illness, the group of symptomatic LEOs most likely had more than one type of illness.…”
Section: Discussioncontrasting
confidence: 61%
“…The consensus of the scientific community remains that illness from unintentional exposures is extremely unlikely, because opioids are not efficiently absorbed through the skin and are unlikely to be carried in the air [8]. In a rare case report of law enforcement officer opioid exposure in a peer-reviewed literature, clinical manifestations were not consistent with opioids, and none of the law enforcement officers tested was positive for opioid metabolites [9]. In other words, the phenomenon of first responder opioid exposure that seemed to be frequently reported in news media has not been confirmed scientifically.…”
mentioning
confidence: 99%
“…9 With each encounter, the lives of first responders are put at risk, as exposure is a serious threat that requires training to ensure that personnel are protected. 10,11 In addition, guidance for first responders during the COVID-19 pandemic may conflict or complicate guidelines for responding to opioid exposure incidents. For example, although the use of hand sanitizer is recommended as a countermeasure against SARS-CoV-2, it is not recommended when opioids may be present, as it can increase the absorption of opioids through the skin.…”
Section: Introductionmentioning
confidence: 99%